Operational performance of a PV generator feeding DC shunt and induction motors with MPPT - Mohammed I. Abuashour; Tha'er O. Sweidan; Mohammad S. Widyan; Mohammed M. Hattab; Mohammed A. Ma'itah (Institute of Advanced Engineering and Science, 2019)
This paper presented the transient and operational behavior of a parallel Combination of DC Shunt Motor and IM fed by a photovoltaic generator at different solar irradiance levels. The maximum power point of current/voltage (I/V) characteristic of the PV generator was achieved for different solar intensities, by utilizing an open circuit voltage method. The nonlinear operational behavior of (I/V) characteristics of the PV generator at various solar intensities and the magnetization curve of the ferromagnetic material of the DC shunt motor were both modeled by high order polynomial mathematical expressions. The study investigated the response of the system at different solar irradiance levels and changing the torque loads for both motors and then following step change in solar intensity levels with fixed loading torques for both motors. All numerical simulations were executed using MATLAB software.